Continuous dyeing processes for zipper tape in supercritical carbon dioxide. (1st August 2017) - Huang, Tingting; Cui, Hongsheng; Yang, Dafa; Kong, Xiangjun; Lin, Jinxin
Abstract: Supercritical carbon dioxide (SC-CO2 ) dyeing is an ecological waterless dyeing method without any dyeing auxiliaries and waste water discharge. In this paper, we introduce continuous dyeing processes of zipper tape in SC-CO2 while recycling the gas simultaneously. Compared to water dyeing, this new processes could reduce CO2 gas consumption and increase production efficiency, and lead to 20% cost decrease. The dyed products also present excellent color fastness to fading, staining, drying, and wetting, which are all rated at a grade of 4–5. The dyed zipper tapes show excellent shade consistency by different dyeing autoclaves, proving that this continuous processes is suitable for the rapid and diverse color change of smaller lots.